2021
DOI: 10.26650/eor.2021922696
|View full text |Cite
|
Sign up to set email alerts
|

The effects of final irrigants on the push-out bond strength of two calcium silicate-based root canal sealers: an in vitro study.

Abstract: PurposeThe purpose of the present study was to investigate the effect of the different irrigant combinations used in final irrigation on the push-out bond strength of root canal sealers that have different compositions. Materials and MethodsIn total 60 dentinal slices in 1 mm thickness were collected from 15 extracted mandibular premolar teeth; 4 slices from each tooth. 3 canal-like artificial cavities were opened on each dentinal slice. Samples were divided into 4 experimental groups, each of which consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…However, as this expansion had no effect with its thin film thickness on the LC technique, an obvious lack of significant differences between Endoseal MTA and Total Fill BC were noticed. [13] In contrary, Celik et al [50] and Silva et al [59] found lower push-out bond strength records for Endoseal MTA sealer than AH Plus. This could be because they evaluated the sealers' bond strength for cavities only generated and filled in root slices, rather than after obturating the entire canal with a gutta percha, as was done in the current investigation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, as this expansion had no effect with its thin film thickness on the LC technique, an obvious lack of significant differences between Endoseal MTA and Total Fill BC were noticed. [13] In contrary, Celik et al [50] and Silva et al [59] found lower push-out bond strength records for Endoseal MTA sealer than AH Plus. This could be because they evaluated the sealers' bond strength for cavities only generated and filled in root slices, rather than after obturating the entire canal with a gutta percha, as was done in the current investigation.…”
Section: Discussionmentioning
confidence: 96%
“…The development of covalent bonds among the epoxide rings and the amino groups in the bare collagen network of dentin, with exceptional adhesion capabilities, was attributed to the superior push-out bond strength in previous studies. [48][49][50] Furthermore, the moderate acidity of AH Plus may result in dentine self-etching as the sealer is introduced into the dentinal tubules by LC pressures, improving interfacial bonding. [28,51,52] Moreover, being chemically cured, AH Plus compensates for the polymerization shrinkage without the development of polymerization stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All samples were mechanically instrumented by rotary files up to size 40 with a continuous taper of 0.4. Although some studies used a diamond or carbide bur in preparing a simulation of a root canal to standardize the diameter of the filling material 12,[46][47][48][49] , the current study was intended to provide information in a clinically oriented setup; therefore, root canals were mechanically prepared in a manner that is commonly used by clinicians and in accordance with other studies. 6,50,51 Recapitulation was performed between each file change using a k-file of size 15, in conjunction with 1 mL of 2.5% sodium hypochlorite irrigation, using a sideperforated needle to avoid debris accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Where SD= Standard deviation of push-out bond strength value of apical section estimated from previous study (22) , and Δ 2 = effect size estimated to be 0.35 between the samples, α = Level of significance, and 1−β = Power. N= (1.96+0.84) 2 *2*(0.34) 2 / (0.35) 2 =14.79 Accordingly, 15 teeth were used in each group with total sample 60 teeth.…”
Section: Sample Sizementioning
confidence: 99%